2018
DOI: 10.1007/s10534-018-0128-0
|View full text |Cite
|
Sign up to set email alerts
|

High Selenium Yeast mitigates aluminum-induced cerebral inflammation by increasing oxidative stress and blocking NO production

Abstract: High Selenium Yeast (SeY) serves many important roles with respect to the maintenance of normal nervous system functioning. Studies have reported the nerve inflammation induced by Aluminum (Al) was associated with the increase of mortality. However, in-depth studies are required to verify the hypothesized neuro-protective efficacy of SeY against Al-induced cerebral damage through modulation of the inflammatory response. Here, mice were treated with SeY (0.1 mg/kg) and/or Al (10 mg/kg) by oral gavage for 28 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 58 Previous investigations examining Se or SeNPs have indicated their abilities to improve the activities and expression of endogenous antioxidant proteins and suppress ROS production following neuronal damage. 66 , 75 , 76 Chitosan-stabilized Se nanoparticles also displayed more antioxidant power toward acrylamide-induced neural damage, as demonstrated by reduced cerebral MDA and NO levels and increased GSH levels. 77 The antioxidant potential of PDGs may also be associated with free radical-scavenging properties and the ability to interfere with NOS activity to suppress NO production.…”
Section: Discussionmentioning
confidence: 95%
“… 58 Previous investigations examining Se or SeNPs have indicated their abilities to improve the activities and expression of endogenous antioxidant proteins and suppress ROS production following neuronal damage. 66 , 75 , 76 Chitosan-stabilized Se nanoparticles also displayed more antioxidant power toward acrylamide-induced neural damage, as demonstrated by reduced cerebral MDA and NO levels and increased GSH levels. 77 The antioxidant potential of PDGs may also be associated with free radical-scavenging properties and the ability to interfere with NOS activity to suppress NO production.…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that the epileptic mice treated with selenium showed a decrease in NO generation due to the inhibition of NOS. Cao et al 59 reported that dietary administration of selenium reversed the increased NO in the cerebral tissue following aluminum exposure. The authors attributed this reduction to the ability of selenium to down-regulate NOS.…”
Section: Dovepressmentioning
confidence: 99%
“…Adding selenium to feed can also effectively reduce the damage caused by inflammation. For example, in mice, Se-Y can inhibit neuroinflammation caused by inorganic aluminum, including the disorder of inflammatory factor expression and the imbalance of the redox system [13]. In addition, selenium is also a commonly used antioxidant in poultry breeding and is mainly used to improve the production performance of poultry and for the production of selenium-rich eggs [7,14].…”
Section: Introductionmentioning
confidence: 99%